How professional training impacts teaching innovation among ideological and political teachers: the mediating and moderating role of basic psychological needs satisfaction - Cui, Can; Yin, Yanjun (Frontiers in Psychology, 2023)
The aim of this study is to explore the impact of professional training on teaching innovation among senior high school ideological and political teachers. By introducing the concept of basic psychological needs satisfaction as a mediating factor, the study seeks to uncover the mechanisms and patterns that manifest in teaching innovation within the Chinese cultural context. To gather empirical data, a questionnaire survey was administered to a sample of 780 teachers in this specialized field. The results showed that providing more professional training is an effective way to enhance teaching innovation. Drawing on Self-Determination Theory, the satisfaction of basic psychological needs (competence, relatedness, and autonomy) was found to play an important role in this process. Competence need satisfaction and relatedness need satisfaction played a mediating role, while autonomy need satisfaction played a moderating role. Based on these findings, several recommendations are provided to support the professional training of senior high school ideological and political teachers and enhance their innovation, including providing personalized training programs, building a mentor system, and allowing greater autonomy in school management.